Effects of Reality Therapy on Drug Cravings and Mental Health of Clients of Therapeutic Community Centers - Parvin Sadat Hosseini; Zahra Eftekhar Saadi; Reza Johari Fard (Iran University of Medical Sciences, 2023)
Background: Substance abuse disorders are associated with serious medical and psychiatric problems. Besides the undesirable side effects following drug-assisted treatment in drug abusers, sudden discontinuation of drug use can cause unpleasant symptoms. This study investigated the impact of reality therapy (RT) on drug cravings and mental health among clients of therapeutic community (TC) centers in Ahvaz City, Iran, in 2022. Methods: This quasi-experimental study adopted a pre-test-post-test design with a control group. The study population consisted of all clients of TC centers of Ahvaz in 2022. Of whom 40 clients were selected as the sample using convenience sampling. In the next step, they were randomly assigned into the experimental and control groups (20 subjects in each group). The data were collected by using the desires for drug questionnaire (DDQ) and the general health questionnaire 28 (GHQ-28). The subjects in the experimental group attended eight 90-minute sessions of RT, whereas those in the control group received no intervention. The obtained data were analyzed using analysis of covariance. The significance level of all tests was considered to be ≤0.05. Results: RT significantly affected drug cravings and mental health of the clients of TC centers (P<0.001). Conclusion: Based on the study findings, RT is recommended for reducing drug cravings and improving mental health of people undergoing drug rehabilitation.